PCL covered PP meshes plasma-grafted by sulfonated monomer for the prevention of postoperative abdominal adhesions. (March 2021) - Dufay, Malo; Jimenez, Maude; Casetta, Mathilde; Chai, Feng; Blanchemain, Nicolas; Stoclet, Grégory; Cazaux, Frédéric; Bellayer, Séverine; Degoutin, Stéphanie
Graphical abstract: Highlights: Polypropylene abdominal implants were covered with polycaprolactone nanofibers. Nanofibers functionalization with sulfonated monomer by cold plasma was optimized. Nanofibrous structure was maintained after surface modification. Functionalized implants did not release any cytotoxic coumpounds. Optimal functionalized implants present anticoagulant activity close to heparin. Abstract: Abdominal hernia reparation constitutes the second surgical operation in the world with more than 20 million cases per year. However, in more than 50 % of all intra-abdominal operations, postoperative adhesions occur and result in important pain for patients. These adhesions take place after excessive deposition of fibrin between peritoneum and organs within the 7 days after the operation which occurs during the coagulation cascade. For this reason, therapeutic solutions are required to both prevent adhesion and limit the need for a second surgical step. Numerous techniques were described in the past few decades to design biomedical textile implants and, among them, electrospinning shows great interest due to the porous and nanometer diameter range structure of the obtained fibers. In parallel, cold plasma treatment can be used to activate and graft their surface with functional molecules, exhibiting for example antibacterial or anticoagulant properties. This work aims at functionalizing, biodegradable polycaprolactone (PCL) electrospun nanofibers covering polypropylene meshes (PPM) with 2-acrylamido-2-methylpropane sulfonic acid (AMPS) through cold plasma induced graft copolymerization. AMPS was chosen as it contains heparin-like segments, leading potentially to similar anticoagulant effect. First, electrospinning of PCL was optimized by varying process, solution and environmental parameters and allowed to select a solution of 12 % of PCL in formic/acetic acid mixture. The graft-copolymerization of AMPS was then optimized in terms of power and time of plasma treatment, as well as solution concentration, using experimental design, in order to obtain nanofibers rich in SO3 H groups at their surface. At each step of the process, the material was thoroughly characterized proving the presence of AMPS onto the surface of the nanofibers. The cytocompatibility and anticoagulant properties, evaluated after sterilization, are promising for an anti-adhesive application of these nanofibrous mats with no release of cytotoxic compound.